2012
DOI: 10.3390/molecules17078118
|View full text |Cite
|
Sign up to set email alerts
|

Food-Related Compounds That Modulate Expression of Inducible Nitric Oxide Synthase May Act as Its Inhibitors

Abstract: Natural compounds commonly found in foods may contribute to protect cells against the deleterious effects of inflammation. These anti-inflammatory properties have been linked to the modulation of transcription factors that control expression of inflammation-related genes, including the inducible nitric oxide synthase (iNOS), rather than a direct inhibitory action on these proteins. In this study, forty two natural dietary compounds, known for their ability to exert an inhibitory effect on the expression of iNO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 82 publications
1
8
0
2
Order By: Relevance
“…4. The correlation analysis indicated the inhibition of DNMT1 activity follows a highly dependence with calculated binding scores for these compounds (r= 0.83, p value <0.0001; for binding affinity vs logIC50, r= 0.65, p value <0.0001; for Total score vs logIC50), with correlation coefficients comparable to those reported in other studies for these validations[56,59,60,73] as shown inFig. 4a and Fig.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…4. The correlation analysis indicated the inhibition of DNMT1 activity follows a highly dependence with calculated binding scores for these compounds (r= 0.83, p value <0.0001; for binding affinity vs logIC50, r= 0.65, p value <0.0001; for Total score vs logIC50), with correlation coefficients comparable to those reported in other studies for these validations[56,59,60,73] as shown inFig. 4a and Fig.…”
supporting
confidence: 69%
“…Based on these results, two representative DNMTs crystallographic structures were selected for protein-ligand docking protocols: DNMT1 (3SWR) and DNMT3A (2QRV). for best poses was taken as the value of the binding affinity for a particular complex [54,59].…”
Section: Preparation and Selection Of Crystallographic Structures Ofmentioning
confidence: 99%
“…Three docking runs were performed for each ligand, and the pose with the highest Affinity absolute value (kcal/mol) was saved. Finally, the mean Affinity score for best poses was taken as the value of the binding Affinity for a particular complex [ 50 , 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…БАКРП способны также изменять биотрансформацию канцерогенов, влиять на репарацию ДНК, экспрессию протоонкогенов, пролиферацию и дифференцировку клеток, апоптоз, эндокринный статус организма, систему противоопухолевого иммунитета и др. [6,66,67]. Растительные полифенолы препятствуют прогрессированию канцерогенеза, в том числе за счет избирательного взаимодействия с белками, образуя полифенольно-белковые комплексы, которые могут влиять на активность онкогенных белков-мишеней.…”
Section: обзорные статьиunclassified
“…Растительные полифенолы препятствуют прогрессированию канцерогенеза, в том числе за счет избирательного взаимодействия с белками, образуя полифенольно-белковые комплексы, которые могут влиять на активность онкогенных белков-мишеней. Следует отметить, что в некоторых случаях, особенно при высоких дозах, БАКРП могут инициировать воспаление, повреждение ДНК и оказывать другие побочные эффекты [66,68].…”
Section: обзорные статьиunclassified